ROLE OF THE ALPHA-1-ADRENOCEPTORS AND ALPHA-2-ADRENOCEPTORS OF THE LATERAL HYPOTHALAMUS IN THE DIPSOGENIC RESPONSE TO CENTRAL ANGIOTENSIN-II IN RATS - Ferrari, A. C.; Camargo, LAD; Saad, W. A.; Renzi, Antonio [UNESP]; Deluca, L. A.; Menani, José Vanderlei [UNESP] (Elsevier B.V., 1991)
The present experiments were conducted to investigate the role of the alpha-1- and alpha-2-adrenergic receptors of the lateral hypothalamus (LH) on the drinking response elicited by intracerebroventricular (i.c.v.) injections of carbachol and angiotensin II (AII) in rats. Clonidine (an alpha-2-adrenergic agonist) injected into the LH produced a dose-dependent reduction of the drinking responses elicited by i.c.v. administration of carbachol and AII. The alpha-1-adrenergic agonist phenylephrine injected into the LH reduced the dipsogenic response to i.c.v. AII, but not to carbachol. Injection of yohimbine (an alpha-2-adrenergic antagonist) and prazosin (an alpha-1-adrenergic antagonist) into the LH also reduced the water intake produced by i.c.v. injection of AII. Previous injection of alpha-1- or alpha-2-adrenergic antagonists into the LH increased the antidipsogenic effect of clonidine or phenylephrine injected into the same area on the water intake induced by i.c.v. AII. These results show that the alpha-1- and alpha-2-adrenergic receptors of the LH are involved in the control of drinking responses elicited by i.c.v. injection of AII in rats. They also show that clonidine, but not phenylephrine, suppresses the drinking induced by i.c.v. carbachol. The data suggest that the discharge of central alpha-adrenergic receptors has a dual (inhibitory and excitatory) effect on water intake induced by central AII.
Keywords: WATER INTAKE; ANGIOTENSIN-II; LATERAL HYPOTHALAMUS; ADRENERGIC RECEPTOR